High-protein diet: biochemical mechanisms, metabolic effects and clinical implications - a narrative review - Polok, Izabela; Łompieś, Kinga; Roczyński, Brajan; Mliczek, Aleksandra; Muszalska, Aleksandra; Wiecanowska, Julia (Quality in Sport, 2026)
Background: High-protein diets are widely used for weight reduction, body composition improvement, and metabolic health. Although effective, concerns remain regarding their long-term safety. This review summarizes current evidence on their benefits and risks. Materials and methods: A narrative review of randomized controlled trials, systematic reviews, meta-analyses, and observational studies evaluated the effects of high-protein diets on metabolic health and potential adverse outcomes. Results: High-protein diets promote weight loss by increasing satiety, thermogenesis, energy expenditure, and preserving fat-free mass. They improve appetite regulation through increased GLP-1 and GIP secretion and reduced ghrelin levels. Benefits are particularly evident in individuals with obesity, insulin resistance, or type 2 diabetes. However, excessive long-term intake, especially from animal sources, may increase renal workload, nephrolithiasis, hyperuricemia, nutritional deficiencies, and possibly cardiovascular risk. Evidence regarding cancer remains inconclusive. Conclusions: When appropriately planned and individualized, high-protein diets are effective for short- and medium-term weight management. Their long-term safety depends on protein source, dietary quality, and individual health status. Further long-term studies are needed to define their role in clinical practice.